The gender gap in political psychology - Lönnqvist, Jan-Erik (Frontiers in Psychology, 2022)
I investigated the authorship gender gap in research on political psychology. The material were 1166 articles published in the field’s flagship journal Political Psychology between 1997 and 2021. These were rated for author gender, methodology, purpose, and topic. Women were underrepresented as authors (37.1% women), single authors (33.5% women), and lead authors (35.1% women). There were disproportionately many women employing interviews or qualitative methodology, and in research with an applied purpose (these were all less cited), whereas men were overrepresented in quantitative research. Regarding topics, women were overrepresented as authors on Gender, Identity, Culture and Language, and Religion, men as authors on Neuroscience and Evolutionary Psychology. The (denigrated) methods, purposes, and topics of women doing research on politics corresponds to the (denigrated) “feminine style” of women doing politics—grounding knowledge in the concrete, lived reality of others, listening and giving voice to marginalized groups subjective experiences, and yielding power to get things done for others.